Bacteroides Fragilis Supernatant Plays Anti-Viability Roles Accompanied by Apoptosis and Cell Cycle Arrest via P62/Caspase8/ Bax/Fas Pathway in Colorectal Adenocarcinoma Cell Line: Anticancer effects of B. fragilis - Daroon Parvar, Mohammad; Rafiee, Aras; Riazi-Rad, Farhad; Katebi, Asal; Shahi, Zahra (Iranian Journal of Pharmaceutical Sciences, 2023)
From two classes of Bacteroides fragilis, enterotoxigenic B. fragilis (ETBF) is associated with colorectal cancer (CRC), yet several non-toxigenic B. fragilis (NTBF) confers powerful health benefits to the host and may be potential probiotic. In this study, the HT-29 cell line was treated with the supernatant of NTBF strain ATCC-23745. Then, the expression level of mTOR /p62/Caspase8/Bax proposed signaling pathway and cell viability, cell apoptosis, and cell cycle progression were determined using Real-time PCR and flow cytometry, respectively. We found that the B. fragilis supernatant inhibited cell proliferation and increased cell apoptosis in a dose- and time-dependent manner. Further, the arrest of the HT-29 cells at the G1 and sub-G1 phases also signified apoptotic cell death after 24 and 72h. The gene expression study revealed that the supernatant significantly up-regulated the Caspase8/Bax/Fas-mediated apoptosis signaling while suppressing the anti-apoptotic mTOR and p62 expression. Our findings suggest that the NTBF ATCC-23745 strain may be a potential probiotic and can be used in CRC treatment.